The Fray on the Meadow: Violence and a Moment of Government in Early Tudor England. (29th December 2017) - Healey, Jonathan
Abstract: On 14 September 1534, two men fought on a meadow outside the town of Weymouth, Dorset, watched by a crowd of their neighbours. Learning of the fight, one of the town constables charged between the men, and killed one of them, leading to his prosecution and subsequent appeal to the court of Star Chamber. The investigation by that court left several thousand words of testimony, making it one of the best documented fights in the sixteenth century. This article offers a microhistory of the fight. In particular, it asks what such an event can tell us about the nature of government in the early Tudor period. It suggests that at this time such flashpoints were crucial moments where the state was expected to play a dramatic role. But this in turn depended on participants performing their role as state actors. That could be very dangerous, but detailed reconstructions can also show how state actors, though lacking the visual symbolic apparatus we expect of the modern state, might deploy oral performances to signify their official role.